Automobile carpet and manufacturing method thereof
By introducing low-melting point bicomponent fibers and recycled black PET fibers into the blanket and suede of automotive carpets, the shortcomings of existing automotive carpets in terms of environmental protection, wear resistance and gloss are solved, and environmentally friendly, wear-resistant and low-gloss effects are achieved, improving the user experience.
Patent Information
- Application Number
- CN202411554596.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Existing automotive carpets have shortcomings in terms of environmental protection, wear resistance and gloss, which are difficult to meet the requirements of environmental protection, low toxicity and high wear resistance. At the same time, the high gloss in high light environments affects the comfort of use.
Using a manufacturing method without adding glue, the carpet is enhanced by introducing low-melting bicomponent fibers into the blanket and suede layer, using them to melt bond PET fibers, stiffness and wear resistance of the carpet are enhanced, and the gloss of the carpet is reduced by recycling black PET fibers and adding titanium dioxide.
It realizes an environmentally friendly and odorless car carpet, with ultra-high wear resistance and long service life, and at the same time, it has low gloss and will not dazzling under strong light, which improves the user experience.
Smart Images

Figure CN119041102B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an automobile carpet and a manufacturing method thereof, and belongs to the field of textile industry manufacturing technology. Background Art
[0002] As environmental protection requirements gradually increase, new requirements are also put forward for the environmental protection and low toxicity performance of automotive interior materials. Usually, in order to achieve a certain hardness and shaping effect, a large amount of liquid glue or latex needs to be added to the automotive carpet. These liquid glues or latex contain high levels of toxic and odorous components, which are difficult to meet the current requirements for low toxicity and environmental protection of automotive interiors; at the same time, automotive end consumers have higher and higher requirements for the wear resistance of automotive carpets; in addition, automotive needle-punched carpets need to adapt to different lighting environments around the world, especially when used in high-light areas, the carpets need to have a lower gloss to improve consumer comfort.
[0003] In the prior art, conventional 300g / m²-600g / m² needle-punched carpets require 20g / m²-200g / m² of SBR styrene-butadiene glue or other water-based foamed latex. The waste glue after production needs to be treated multiple times before it can be discharged, which pollutes the environment and increases the processing cost of the carpet. In addition, the current needle-punched carpets are mostly produced by re-spinning fibers from PET waste materials such as discarded mineral water bottles. The fiber breaking strength is poor, resulting in weak wear resistance of the carpet. The conventional Taber wear test (500g load) can only achieve 200~1000 laps. If it exceeds 1000 laps, the bottom will be obviously exposed, and some fibers will be pulled out to exceed the height of the carpet plane by more than 3mm. At the same time, the current needle-punched carpets have many reflection points under strong light, especially between 12 noon and 1 o'clock, the carpet's luster is relatively dazzling, which will cause discomfort to drivers or passengers. Summary of the invention
[0004] In order to solve the above problems, a car carpet and a manufacturing method thereof are provided. No glue needs to be added during the manufacturing process of the car carpet, so the car carpet is environmentally friendly and odorless, and has ultra-high wear resistance and a long service life. In addition, the carpet has a low glossiness and will not be dazzling under strong light, which can enhance the user's experience of use.
[0005] According to one aspect of the present application, a car carpet is provided, which comprises a connected carpet embryo layer and a suede layer, wherein the suede layer comprises a plurality of fiber bundles, wherein the fiber bundles at least partially extend into the carpet embryo layer in the longitudinal direction, and the fibers of the carpet embryo layer and the suede layer are both composited with PET fibers and low-melting-point bicomponent fibers.
[0006] The weight of the low-melting bicomponent fiber accounts for 3%-10% of the weight of the blanket embryo layer, preferably 5%, and the weight of the low-melting bicomponent fiber accounts for 3%-10% of the weight of the suede layer, preferably 5%.
[0007] By introducing low-melting-point bicomponent fibers into the carpet embryo layer and the suede layer, the PET fibers can be melt-bonded during the carpet shaping process, thereby enhancing the bonding effect between the PET fibers and the low-melting-point bicomponent fibers, thereby improving the stiffness and wear resistance of the carpet.
[0008] By controlling the amount of low-melting-point bicomponent fiber added, we can prevent the poor bonding between PET fiber and low-melting-point bicomponent fiber caused by too low an amount added, and avoid excessive stiffness of the carpet caused by too high an amount added, thereby ensuring that the carpet has a certain softness and improving the user experience.
[0009] Optionally, the bicomponent fiber is a sheath-core bicomponent fiber with a fineness of 2D-15D, the core of the bicomponent fiber is polyethylene terephthalate, and the sheath of the bicomponent fiber is modified polyethylene terephthalate. The bicomponent fiber preferably has a fineness of 10D.
[0010] Optionally, the modified polyethylene terephthalate is obtained by reacting ethylene glycol with isophthalic acid after replacing part of terephthalic acid, wherein the weight ratio of isophthalic acid to terephthalic acid is 0.01-0.3:1, preferably 0.1:1.
[0011] By using polyethylene terephthalate (PET) as the core of the two-component fiber, the original PET form can be maintained. Due to its large molecular weight, the fiber's wear resistance and tensile strength and other properties can be improved, thereby ensuring the wear resistance and service life of the carpet; by using isophthalic acid to replace part of terephthalic acid to prepare modified polyethylene terephthalate (modified PET), a block structure of two different esterified link units is formed in the PET molecular chain, which can destroy the regularity of the PET molecular chain. Among them, the ethylene terephthalate unit maintains rigidity, and the ethylene isophthalate unit ensures flexibility, reducing high crystallinity, and the melting range of the modified PET can be reduced to 110°C-160°C. The modified PET is used as the skin of the two-component fiber. Due to its low initial melting point, it can begin to melt at 110°C. After the temperature rises, its flowability is better, so it can more fully bond to the surrounding fibers, enhance the rigidity and wear resistance of the carpet, and can improve the elongation of the carpet, which is conducive to the molding of the carpet.
[0012] In addition, by controlling the addition ratio between isophthalic acid and terephthalic acid, the carpet is guaranteed to have both strong rigidity and wear resistance, as well as certain flexibility and elongation. By controlling the fineness of the two-component fiber, the carpet is further guaranteed to have high mechanical strength and appropriate flexibility.
[0013] It is understandable that the preparation process of PET prepared by reacting terephthalic acid and ethylene glycol is a prior art. The preparation process of the modified PET in this application only needs to replace part of the terephthalic acid with isophthalic acid, and the rest of the preparation process is the same as the existing PET preparation process.
[0014] Optionally, the PET fiber is produced by spinning modified black PET chips and white PET chips, and the cross-section of the PET fiber is a circular cross-section, and the cross-section profile is 1.
[0015] By controlling the cross-section of the PET fiber obtained by spinning to be circular, the wear resistance of the carpet can be further improved, and the cross-sectional profile is low, which makes it difficult for light projected onto the carpet to gather, thereby reducing the glossiness of the carpet.
[0016] It is understandable that the carpet referred to in this application includes numerous interior carpets inside the car, such as the main car carpet, trunk carpet, center console trim, seat back fabric, AB pillar lower fabric, etc.
[0017] Optionally, the preparation method of the black PET chips is: the recycled black PET fibers are dried, melted, purified, cooled, stretched and pelletized to obtain the black PET chips.
[0018] The preparation method of the white PET slices is: terephthalic acid and ethylene glycol are mixed to obtain a mixed slurry, titanium dioxide is added to the mixed slurry, and the white PET slices are obtained by reaction, wherein the mass fraction of the titanium dioxide matting agent in the mixed slurry is 0.25%-5%.
[0019] It is understandable that the recycled black PET fiber can be obtained from recycled bottle preforms, bottle flakes or waste monofilaments.
[0020] By using recycled black PET fiber as raw material to prepare black PET chips, black PET waste can be reused to save resources. More importantly, the polymerization degree and crystallinity of recycled materials are low, so as raw materials for making carpets, the glossiness of carpets can be reduced. By adding titanium dioxide as a matting agent to white PET chips, the glossiness of the finished carpet can be further reduced.
[0021] Preferably, in the method for preparing black PET slices, carbon nanotubes modified with a silane coupling agent are added during the melting process of the recycled black PET; wherein the weight ratio of the carbon nanotubes modified with a silane coupling agent to the recycled black PET is 0.001-0.01:1.
[0022] The preparation method of carbon nanotubes modified by silane coupling agent is as follows: immersing carbon nanotubes in 3.5-4.5 mol / L concentrated sulfuric acid, dispersing them evenly and immersing them for 30-40 hours, cooling and washing them to neutrality to obtain activated carbon nanotubes; adding the activated carbon nanotubes and silane coupling agent to toluene, stirring them evenly and reacting them for 15-25 hours, cooling and washing them to obtain carbon nanotubes modified by silane coupling agent, wherein the weight ratio of activated carbon nanotubes to silane coupling agent is 1:1-1.5.
[0023] As a polymer, the low-energy functional groups contained in PET are difficult to form a good interaction with the high-energy functional groups of carbon nanotubes. The silane coupling agent can react with the hydroxyl or carboxyl groups on the surface of the carbon nanotubes, and the organic groups of the silane molecules can react with the functional groups on the surface of the polymer to form a bond structure, thereby improving the compatibility between the polymer and the carbon nanotubes; carbon nanotubes have good light absorption properties, so they can further reduce the gloss of the carpet; in addition, carbon nanotubes have excellent mechanical properties, and they have strong tensile strength and rigidity, so they can improve the wear resistance of the carpet and extend the service life of the carpet.
[0024] Optionally, the weight fraction of the black PET slices to the PET fiber is 2%-20%; the fineness of the PET fiber is 2D-18D. This setting can reduce the glossiness of the carpet and improve the user experience. In addition, it can also improve the fiber's anti-fracture ability, improve the carpet's wear resistance, and extend the carpet's service life.
[0025] Optionally, the needle punching density of the blanket embryo layer is 350-450 l / cm², and the gram weight of the blanket embryo layer is 450-550 g / m 2 This arrangement can improve the bonding strength between the carpet embryo layer and the suede layer, prevent the fiber bundles from being pulled out in the form of pile, and can enhance the cohesion and bonding strength between the fibers in the carpet embryo layer, prevent the fibers from being pulled out in the form of a single or multiple fibers, and increase the wear resistance of the carpet.
[0026] Optionally, the fiber bundle density in the suede layer (i.e., the pile density of the suede layer) is 350-500p / cm 2 The number of fibers in the fiber bundle is 1-4. This arrangement can prevent the fiber bundle from being pulled out in the form of pile, while improving the mechanical strength of the fiber bundle, preventing the pile layer from falling off and generating debris during use, and ensuring the cohesion and bonding strength between the fibers in the fiber bundle, preventing the fibers from being pulled out in the form of a single or multiple fibers, thereby increasing the wear resistance of the carpet.
[0027] According to another aspect of the present application, a method for manufacturing the automotive carpet described in any one of the above items is provided, characterized in that it comprises the following steps:
[0028] (1) PET fiber and low melting point bicomponent fiber are opened and mixed in a predetermined ratio, and then combed and laid to form a fiber web.
[0029] (2) Punching the fiber web from top to bottom by a needle punching machine to make the PET fiber and the low melting point bicomponent fiber embrace each other, and the needle punching depth of the needle punching machine is 5-10 mm; and raising the pile by a pile raising machine to form the direction of the carpet, thereby obtaining a semi-finished carpet;
[0030] (3) placing the semi-finished carpet into an oven for shaping to obtain the automotive carpet, with a shaping speed of 6-12 m / min and a shaping time of 2-5 min.
[0031] By controlling the shaping parameters of the carpet, it is possible to ensure that the carpet is fully shaped, thereby ensuring the carpet's wear resistance.
[0032] Optionally, in step (3), the temperature of the oven is 150-210° C. This temperature can ensure that the bicomponent fibers are fully melted, thereby ensuring the bonding performance between the bicomponent fibers and the PET fibers and improving the wear resistance of the carpet.
[0033] The beneficial effects of this application include but are not limited to:
[0034] 1. The automotive carpet of the present application, by introducing low-melting-point bicomponent fibers into the carpet embryo layer and the suede layer, can melt-bond PET fibers during the carpet shaping process, thereby enhancing the bonding effect between the PET fibers and the low-melting-point bicomponent fibers, thereby improving the stiffness and wear resistance of the carpet.
[0035] 2. The automotive carpet of the present application can maintain the original PET form by using polyethylene terephthalate (PET) as the core of the two-component fiber. Due to its large molecular weight, it can improve the fiber's wear resistance and tensile strength, thereby ensuring the wear resistance and service life of the carpet; by using isophthalic acid to replace part of terephthalic acid to prepare modified polyethylene terephthalate (modified PET), a block structure of two different esterified chain units is formed in the PET molecular chain, which can destroy the PET molecular chain. The regularity of the sub-chain, wherein the ethylene terephthalate unit maintains rigidity, the ethyl isophthalate unit ensures flexibility, and reduces the high crystallinity. The melting range of the modified PET can be reduced to 110°C-160°C. The modified PET is used as the sheath of the two-component fiber. Due to the low initial melting point, it can begin to melt at 110°C. After the temperature rises, its flowability is better, so it can more fully bond to the surrounding fibers, enhance the rigidity and wear resistance of the carpet, and can improve the elongation of the carpet, which is beneficial to the molding of the carpet.
[0036] 3. The automotive carpet of the present application uses recycled black PET fibers as raw materials to prepare black PET slices, which can reuse black PET waste and save resources. More importantly, the polymerization degree and crystallinity of the recycled materials are low, so the glossiness of the carpet can be reduced when used as raw materials for making carpets. The glossiness of the finished carpet can be further reduced by adding titanium dioxide as a matting agent to the white PET slices.
[0037] 4. The automotive carpet of the present application can improve the bonding strength between the carpet embryo layer and the suede layer, prevent the fiber bundles from being pulled out in the form of pile, and can enhance the cohesion and bonding strength between the fibers of the carpet embryo layer, prevent the fibers from being pulled out in the form of a single strand or multiple strands, and increase the wear resistance of the carpet. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0039] Figure 1 This is a structural schematic diagram of the automotive carpet 1# involved in Example 1 of the present application;
[0040] Figure 2 This is a scanning electron microscope image of the fibers in the automotive carpet 1# involved in Example 1 of the present application after 2000 cycles of the Taber abrasion test (1 kg load);
[0041] Figure 3 This is a photo of the automotive carpet D1# in this embodiment before the Taber wear test.
[0042] Figure 4 This is a photo of the automotive carpet D1# in this embodiment after 1000 cycles of the Taber abrasion test (1 kg load). DETAILED DESCRIPTION
[0043] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0044] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application were purchased through commercial channels.
[0045] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art.
[0046] Example 1 Carpet 1#
[0047] The preparation process of PET fiber 1# is as follows: terephthalic acid and ethylene glycol in a weight ratio of 1:1.2 are mixed to obtain a mixed slurry, and an esterification reaction is carried out at 150°C and a pressure of 80KPa for 90 minutes. Titanium dioxide is then added, and the temperature is raised to 230°C for a reduced pressure polycondensation reaction. After continuing the reaction for 60 minutes, white PET chips are obtained, in which the mass fraction of titanium dioxide in the mixed slurry is 2.5%.
[0048] The recycled black PET fiber is dried and added into an extruder for melting (temperature is 270°C). After filtering and purification, it is cooled and stretched at a cooling temperature of 80°C. Black PET chips are obtained after pelletizing.
[0049] 10 parts by weight of black PET chips, 90 parts by weight of white PET chips and 2-5 parts by weight of masterbatch materials are spun to produce PET fiber 1#, the cross section of the fiber is circular, the cross section profile is 1, and the fineness is 12D;
[0050] The preparation process of low melting point bicomponent fiber 1# is as follows:
[0051] 10 parts by weight of isophthalic acid and 100 parts by weight of terephthalic acid are mixed with 120 parts by weight of ethylene glycol to obtain a mixed slurry, and an esterification reaction is carried out at 150°C and a pressure of 80 KPa for 90 min. The temperature is raised to 230°C for a reduced pressure polycondensation reaction, and the reaction is continued for 60 min to obtain modified PET. With PET as the core and the modified PET as the sheath, a sheath-core type low-melting-point two-component fiber 1# with a fineness of 10D is prepared using a sheath-core type composite spinning assembly.
[0052] The preparation process of carpet 1# is as follows:
[0053] (1) PET fiber 1# and bicomponent fiber 1# are opened in a predetermined ratio, and after the fibers are loosened, each fiber is combed by a cylinder, and a fiber web 1# is formed after a web laying operation, wherein the amount of the bicomponent fiber 1# added is 5 parts, and the amount of the PET fiber 1# added is 95 parts;
[0054] (2) The fiber web 1# is needled and reinforced from different directions from top to bottom by a high-speed needle punching machine, so that the PET fiber 1# and the bicomponent fiber 1# can be tightly bonded together. The needle punching depth of the needle punching machine is 8 mm and the needle punching density is 400 l / cm 2 , weight 550g / m 2 Then the pile is hooked up by the pile needle and the pile brush of the high stability pile raising machine to form the direction of the carpet, and the semi-finished carpet 1# is obtained, wherein the pile density in the pile surface layer is 400-420 p / cm 2; The number of fibers in the fiber bundle is 1-4;
[0055] (3) The semi-finished carpet #1 is placed in an oven for shaping to obtain the automotive carpet #1; wherein the shaping speed is 8 m / min, the shaping time is 3 min, and the oven temperature is 180°C.
[0056] Figure 1 Schematic diagram of the structure of the car carpet in this embodiment, wherein the upper layer is a suede layer, and the lower layer is a carpet embryo layer. Under the action of acupuncture, a single fiber or a plurality of fibers forming a fiber bundle are partially punctured to form a suede layer.
[0057] Example 2 Carpet 2#
[0058] The difference between carpet 2# and carpet 1# is that in the preparation step (1), the amount of bicomponent fiber 1# added is 10 parts, and the amount of PET fiber 1# added is 90 parts; the remaining steps are the same.
[0059] Example 3 Carpet 3#
[0060] The difference between carpet 3# and carpet 1# is that the core of the two-component fiber is PET and the sheath is polypropylene; the rest of the steps are the same.
[0061] Example 4 Carpet 4#
[0062] The difference between carpet 4# and carpet 1# is that: during the preparation of the low melting point bicomponent fiber, 25 parts by weight of isophthalic acid and 100 parts by weight of terephthalic acid are added to obtain bicomponent fiber 2#; during the preparation of carpet 4#, bicomponent fiber 2# is used instead of bicomponent fiber 1# in step (1), and the remaining steps are the same.
[0063] Example 5 Carpet 5#
[0064] The difference between carpet 5# and carpet 1# is that: in the preparation process of PET fiber 1#, black PET is not added to obtain PET fiber 2#; in the preparation process of carpet 5#, PET fiber 2# is used instead of PET fiber 1# in step (1), and the remaining steps are the same.
[0065] Example 6 Carpet 6#
[0066] The difference between carpet 6# and carpet 1# is that: in the preparation process of PET fiber 1#, 20 parts by weight of black PET chips, 80 parts by weight of white PET chips and 2-5 parts by weight of masterbatch are spun to produce PET fiber 3#; in the preparation process of carpet 6#, PET fiber 3# is used instead of PET fiber 1# in step (1), and the remaining steps are the same.
[0067] Example 7 Carpet 7#
[0068] The difference between carpet #6 and carpet #1 is that the recycled black PET fibers are dried and then added to an extruder for melting (at a temperature of 270°C), and carbon nanotubes modified with a silane coupling agent are added. After filtering and purification, the fibers are cooled and stretched at a temperature of 80°C, and pelletized to obtain black PET slices, wherein the weight ratio of the carbon nanotubes modified with a silane coupling agent to the recycled black PET is 0.005:1.
[0069] The preparation method of carbon nanotubes modified by silane coupling agent is as follows: immersing carbon nanotubes in 4 mol / L concentrated sulfuric acid, immersing for 35 hours after uniform dispersion, cooling and washing to neutrality to obtain activated carbon nanotubes; adding 10 parts by weight of the activated carbon nanotubes and 12 parts by weight of the silane coupling agent to toluene, stirring evenly and reacting for 20 hours, cooling and washing to obtain carbon nanotubes modified by silane coupling agent.
[0070] Example 8
[0071] The preparation process of PET fiber 4# is as follows: terephthalic acid and ethylene glycol in a weight ratio of 1:1.2 are mixed to obtain a mixed slurry, and an esterification reaction is carried out at 150°C and a pressure of 80KPa for 90 minutes. Titanium dioxide is then added, and the temperature is raised to 230°C for a reduced pressure polycondensation reaction. After continuing the reaction for 60 minutes, white PET chips are obtained, in which the mass fraction of titanium dioxide in the mixed slurry is 1%.
[0072] The recycled black PET fiber is dried and added into an extruder for melting (temperature is 270°C). After filtering and purification, it is cooled and stretched at a cooling temperature of 80°C. Black PET chips are obtained after pelletizing.
[0073] 10 parts by weight of black PET chips, 90 parts by weight of white PET chips and 2-5 parts by weight of masterbatch materials are spun to produce PET fiber 4#, the cross section of the fiber is a trilobal cross section, the cross section profile is 2.3, and the fineness is 12D;
[0074] The preparation process of low melting point bicomponent fiber 3# is as follows:
[0075] 10 parts by weight of isophthalic acid and 100 parts by weight of terephthalic acid are mixed with 120 parts by weight of ethylene glycol to obtain a mixed slurry, and an esterification reaction is carried out at 150°C and a pressure of 80 KPa for 90 min. The temperature is raised to 230°C for a reduced pressure polycondensation reaction, and the reaction is continued for 60 min to obtain modified PET. With PET as the core and the modified PET as the sheath, a sheath-core type low-melting-point two-component fiber 3# with a fineness of 15D is prepared using a sheath-core type composite spinning assembly.
[0076] The preparation process of carpet 8# is as follows:
[0077] (1) PET fiber 4# and bicomponent fiber 3# are opened in a predetermined ratio, and after the fibers are loosened, each fiber is combed by a cylinder, and a fiber web is formed after a web laying operation, wherein the amount of bicomponent fiber 3# added is 3 parts, and the amount of PET fiber 4# added is 97 parts;
[0078] (2) The fiber web is needled and reinforced from different directions from top to bottom by a high-speed needle punching machine, so that the PET fiber 4# and the bicomponent fiber 3# can be tightly bonded together. The needle punching depth of the needle punching machine is 5mm and the needle punching density is 350l / cm 2 , weight 450g / m 2 Then, the piles are hooked up by the pile needles and pile brushes of the high-stability pile raising machine to form the direction of the carpet, and a semi-finished carpet 1# is obtained, wherein the pile density in the pile surface layer is 350-370 p / cm 2 ; The number of fibers in the fiber bundle is 1-4 (3) The semi-finished carpet is placed in an oven for shaping to obtain automotive carpet 8#; wherein the shaping speed is 12 m / min, the shaping time is 5 min, and the oven temperature is 150°C.
[0079] Comparative Example 1 Carpet D1#
[0080] Carpet D1# is a carpet with glue added available on the market.
[0081] Comparative Example 2 Carpet D2#
[0082] The difference between carpet D2# and carpet 1# is that low melting point bicomponent fiber is not added.
[0083] Comparative Example 3 Carpet D3#
[0084] The difference between carpet D3# and carpet 1# is that in the preparation step (1), the amount of bicomponent fiber 1# added is 2 parts, and the amount of PET fiber 1# added is 98 parts; the remaining steps are the same.
[0085] Test Case
[0086] The transverse breaking strength, longitudinal breaking strength, Taber abrasion resistance, and light aging resistance of carpet 1# to carpet 8# and comparison carpet D1# to D3# were tested, and the glossiness of carpet 1# to carpet 8# and comparison carpet D1# to D3# was tested using a gloss meter. The transverse breaking strength and longitudinal breaking strength were tested according to DIN EN ISO 13934-1, and the Taber abrasion resistance was tested according to ISO 5470-1. The load was 1kg, and an H-18 grinding wheel was used. The light aging resistance was tested according to SAE J2412, and the irradiation amount was 601.6KJ / m 2 The gloss test adopts ISO7668 test standard; the results are shown in Table 1.
[0087] Table 1
[0088]
[0089] It can be seen from the above table that the carpet manufactured in the present application has high mechanical strength, strong wear resistance, and excellent anti-aging ability, which can greatly improve the service life of the carpet. In addition, the glossiness is reduced and it will not be dazzling under strong light, which can improve the user experience.
[0090] Figure 2 This is a scanning electron microscope image of the fibers in the automotive carpet No. 1 in this embodiment after 2000 cycles of Taber abrasion test (1kg load). It can be seen from the figure that after 2000 cycles of abrasion test, the shape of the fibers in the carpet remains unchanged, and there are only slight fiber debris on the surface, indicating that the carpet has ultra-high abrasion resistance and a long service life. After 2000 cycles of Taber abrasion test (1kg load), there are only traces of Taber grinding wheel wear on the surface of the carpet, and no wear-through occurs, and the height of the fiber extraction from the carpet germ layer is less than 2.5mm, indicating that the carpet has ultra-high mechanical strength and wear resistance.
[0091] Figure 3 This is a photo of the automotive carpet D1# in this embodiment before the Taber wear test. Figure 4 This is a photo of the automotive carpet D1# in this embodiment after 1000 cycles of Taber abrasion test (1 kg load). It can be seen that the existing carpet has a significant bottom exposure phenomenon after 1000 cycles of the test.
[0092] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A car carpet, characterized in that: The invention comprises a connected blanket embryo layer and a suede layer, wherein the suede layer comprises a plurality of fiber bundles, wherein the fiber bundles at least partially extend into the blanket embryo layer in the longitudinal direction, and the fibers of the blanket embryo layer and the suede layer are both composited with PET fibers and low-melting-point bicomponent fibers. The weight of the low-melting-point bicomponent fiber accounts for 3%-10% of the weight of the blanket germ layer, and the weight of the low-melting-point bicomponent fiber accounts for 3%-10% of the weight of the suede layer; The bicomponent fiber is a sheath-core bicomponent fiber with a fineness of 2D-15D, the core of the bicomponent fiber is polyethylene terephthalate, and the sheath of the bicomponent fiber is modified polyethylene terephthalate; the modified polyethylene terephthalate is obtained by replacing part of terephthalic acid with isophthalic acid and reacting with ethylene glycol, and the weight ratio of isophthalic acid to terephthalic acid is 0.01-0.3:1; The PET fiber is produced by spinning black PET chips and white PET chips, the cross section of the PET fiber is a circular cross section, and the cross section profile is 1; The mass fraction of the black PET slices in the PET fiber is 2%-20%; the fineness of the PET fiber is 2D-18D; The method for preparing the black PET slice comprises: adding carbon nanotubes modified by a silane coupling agent during the melting process of the recycled black PET; wherein the weight ratio of the carbon nanotubes modified by the silane coupling agent to the recycled black PET is 0.001-0.01:
1.
2. The automotive carpet according to claim 1, characterized in that: The preparation method of the black PET slices is as follows: the recycled black PET fibers are dried, melted, purified, cooled, stretched and pelletized to obtain the black PET slices; The preparation method of the white PET slices is as follows: terephthalic acid and ethylene glycol are mixed to obtain a mixed slurry, titanium dioxide is added to the mixed slurry, and the white PET slices are obtained by reaction, wherein the mass fraction of the titanium dioxide in the mixed slurry is 0.25%-5%.
3. The automotive carpet according to claim 1, characterized in that: The acupuncture density of the blanket germ layer is 350-450 l / cm 2 The weight of the blanket embryo layer is 450-550g / m 2 .
4. The automotive carpet according to claim 3, characterized in that: The fiber bundle density in the suede layer is 350-500p / cm 2 ; The number of fibers in the fiber bundle is 1-4.
5. The method for manufacturing an automotive carpet according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) PET fiber and low melting point bicomponent fiber are opened and mixed in a predetermined ratio, and then combed and laid to form a fiber web. (2) Punching the fiber web from top to bottom by a needle punching machine to make the PET fiber and the low-melting-point bicomponent fiber embrace each other, and the needle punching depth of the needle punching machine is 5-10 mm; and raising the pile by a pile raising machine to form the direction of the carpet, thereby obtaining a semi-finished carpet; (3) placing the semi-finished carpet into an oven for shaping to obtain the automotive carpet, with a shaping speed of 6-12 m / min and a shaping time of 2-5 min.
6. The manufacturing method according to claim 5, characterized in that: In step (3), the temperature of the oven is 150-210°C.
Citation Information
Patent Citations
Composite knitted automobile Carpet and its making process
CN101046033A
Method for manufacturing far infrared-antistatic polyester fiber
CN1763276A
Production of heat-resistant elastic polyester hard wool
JP1997049161A